2006
DOI: 10.1093/hmg/ddl017
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of polyglutamine-induced toxicity in cell and animal models of Huntington's disease by ubiquilin

Abstract: Expanded polyglutamine (polyQ) tracts are associated with the induction of protein aggregation and cause cytotoxicity in nine different neurodegenerative disorders. Here, we report that ubiquilin suppresses polyQ-induced protein aggregation and toxicity in cells and in an animal model of Huntington's disease. Overexpression of ubiquilin in HeLa cells and primary neurons reduced aggregation of polyQ-containing proteins and cell death induced by overexpression of a green fluorescent protein (GFP)-huntingtin fusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
147
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(162 citation statements)
references
References 22 publications
15
147
0
Order By: Relevance
“…Ubqln binds ubiquitinated proteins through the UBA, at the same time binding the proteasome through the UBL; it appears to act as a scaffold to facilitate proteasomal degradation of ubiquitinated proteins that have been exported from the ER (24,25). This function could explain most of the proposed functions of Ubqln, such as regulation of autophagy, unfolded protein response, and interaction with both poly-alanine and poly-glutamine expanded proteins (21,22,(27)(28)(29)(30)41). Additional, nonERAD dependent functions for Ubqln, and related proteins, have also been proposed, including a role in the trafficking of amyloid precursor protein and endocytosis of G-protein coupled receptors (18,21,23,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ubqln binds ubiquitinated proteins through the UBA, at the same time binding the proteasome through the UBL; it appears to act as a scaffold to facilitate proteasomal degradation of ubiquitinated proteins that have been exported from the ER (24,25). This function could explain most of the proposed functions of Ubqln, such as regulation of autophagy, unfolded protein response, and interaction with both poly-alanine and poly-glutamine expanded proteins (21,22,(27)(28)(29)(30)41). Additional, nonERAD dependent functions for Ubqln, and related proteins, have also been proposed, including a role in the trafficking of amyloid precursor protein and endocytosis of G-protein coupled receptors (18,21,23,26).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ubqln has been shown to play a role in a variety of other cellular processes, including autophagy, ER-associated protein degradation (ERAD) and receptor trafficking, presumably by regulating the abundance of proteins implicated in these events (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Furthermore, UBQLN is one member of a family of at least five proteins (UBQLN1, UBQLN2, UBQLN3, UBQLN4, and UBQLNL) that share a high degree of similarity at the level of both amino acid and domain structure.…”
mentioning
confidence: 99%
“…In a previous report we showed that overexpression of ubiquilin suppresses the formation of protein aggregates and toxicity of expanded polyglutamine proteins [15]. Here, we have examined how ubiquilin might exert this protective effect.…”
Section: Introductionmentioning
confidence: 90%
“…The generation of HeLa cell lines stably expressing GFP, or GFP-htt-Exon1-28Q, or GFPhtt-74Q fusion proteins (referred to as GFP, GFP-28Q and GFP-74Q cell lines, respectively) were described previously [15]. The stable cell lines were cultured in DMEM supplemented with 10% FBS and 0.1% (g/m1) of G418 (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, other groups have reported that ubiquilin plays a role in the cellular response to protein misfolding and aggregation (59). Specifically, ubiquilin has been shown to protect against polyglutamine-induced toxicity in cellular and invertebrate models of Huntington's disease (60,61). Ubiquilin is also involved in aggresome formation (62) and may promote removal of cellular aggregates via autophagy (63,64).…”
Section: Ubiquilin-1 Is a Molecular Chaperonementioning
confidence: 99%